Effect of Dietary Minerals on Virulence Attributes of Vibrio cholerae - Bhattaram, Varunkumar; Upadhyay, Abhinav; Yin, Hsin-Bai; Mooyottu, Shankumar; Venkitanarayanan, Kumar (Frontiers in Microbiology, 2017)
Vibrio cholerae is a water-borne pathogen responsible for causing a toxin-mediated profuse diarrhea in humans, leading to severe dehydration and death in unattended patients. With increasing reports of antibiotic resistance in V. cholerae, there is a need for alternate interventional strategies for controlling cholera. A potential new strategy for treating infectious diseases involves targeting bacterial virulence rather than growth, where a pathogen’s specific mechanisms critical for causing infection in hosts are inhibited. Since bacterial motility, intestinal colonization and cholera toxin are critical components in V. cholerae pathogenesis, attenuating these virulence factors could potentially control cholera in humans. In this study, the efficacy of sub-inhibitory concentration (SIC, highest concentration not inhibiting bacterial growth) of essential minerals, zinc (Zn), selenium (Se), and manganese (Mn) in reducing V. cholerae motility and adhesion to intestinal epithelial cells (Caco-2), cholera toxin production, and toxin binding to the ganglioside receptor (GM1) was investigated. Additionally, V. cholerae attachment and toxin production in an ex vivo mouse intestine model was determined. Further, the effect of Zn, Se and Mn on V. cholerae virulence genes, ctxAB (toxin production), fliA (motility), tcpA (intestinal colonization), and toxR (master regulon) was determined using real-time quantitative PCR. All three minerals significantly reduced V. cholerae motility, adhesion to Caco-2 cells, and cholera toxin production in vitro, and decreased adhesion and toxin production in mouse intestine ex vivo (P < 0.05). In addition, Zn, Se, and Mn down-regulated the transcription of virulence genes, ctxAB, fliA, and toxR. Results suggest that Zn, Se, and Mn could be potentially used to reduce V. cholerae virulence. However, in vivo studies in an animal model are necessary to validate these results.